PSEUDO-GROUP SOCIAL CONFLICT WHAT HAPPENED IN THE COMMUNITY POST THE VILLAGE HEAD ELECTION - Yoga Pratama Hardaniwan; Drajat Tri Kartono; Ahmad Zuber (Universitas prof. Dr. Moestopo (Beragama), 2024)
The study aims to delve into the social conflicts that arise post-Village Head Election (Pilkades) in Balongdowo Village, Kepohbaru District, Bojonegoro Regency. It seeks to shed light on the conflict's background, its triggers, and the subsequent social dynamics within the village. Moreover, it intends to examine the steps taken by relevant stakeholders and the local community to resolve the conflict. Employing a qualitative research methodology, the study utilizes descriptive data gathered from informants and the community's behavior. Data collection methods include interviews, observations, and documentation. The findings underscore that the conflict emerges due to the insufficient support from villagers for the village head candidate from their own community, particularly evident in Kampung Karikil, the residence of the elected candidate. The proposed resolution entails mediation with active involvement from the local community.